Novel aspects of systemic sclerosis - Valentini, Gabriele (Henry Stewart Talks, 2018)
Definition of systemic sclerosis, Aspects of the diagnostic process, Pitfalls of using classification criteria for diagnosis, Early diagnosis of systemic sclerosis, Disease marker autoantibodies, Outcomes in patients with Raynaud’s Phenomenon, Haemodynamic definitions of PH, Assessment of distinct organ involvement and of quality of life, Pathology of activity and damage in SSc, Prediction of prognosis and its factors